2019
DOI: 10.3329/bjms.v18i4.42877
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Social Support among Non-Depressed and Depressed Mothers after Childbirth in Jahrom, Iran.

Abstract: The purpose of this study was to evaluate the social support provided for non-depressed women and women with postpartum depression referring to health centers in Jahrom. Method: In order to achieve the mentioned goal, three health care centers randomly selected. 60 referring women who had the required criteria were selected by convenience sampling method and were divided into two groups of postpartum depression (30) and non-depressed (30) people. For evaluation of social support, the Phillips Social Supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…Since education plays a major role in the student's view of professional education, this study examined and highlighted educational needs by examining the views of students on professional curriculum. Precise knowledge of the qualitative and quantitative status of providing educational services in the faculties and medical universities of the country is considered as the first planning step in comparison with each other 24,25 . In this study, it should be noted that although students generally had a positive attitude towards their professional vales, the need to pay more attention and support to different areas of professional duties and to raise awareness about the importance of some professional values in their curriculum is felt.…”
Section: Methodmentioning
confidence: 99%
“…Since education plays a major role in the student's view of professional education, this study examined and highlighted educational needs by examining the views of students on professional curriculum. Precise knowledge of the qualitative and quantitative status of providing educational services in the faculties and medical universities of the country is considered as the first planning step in comparison with each other 24,25 . In this study, it should be noted that although students generally had a positive attitude towards their professional vales, the need to pay more attention and support to different areas of professional duties and to raise awareness about the importance of some professional values in their curriculum is felt.…”
Section: Methodmentioning
confidence: 99%
“…It is well known that postpartum period itself can bring about changes in the mother both mentally and physically, and adequate support should be given to her during this time to prevent the occurrence of any psychological incidents such as postpartum depression. 25 In this case, the mother was already in a traumatic state with the loss of one child as well as due to her physical weakness and mentally debilitated state.She was counselled appropriately, and was in regular checkup from us as well as by the obstetricians. Special care was taken regarding her diet to ensure her speedy recovery.…”
Section: Discussionmentioning
confidence: 94%
“…Our results showed the incidence of high PPD symptoms, which indicated the mothers whose depressive symptom scores were above 13, was acquired at 24%. In similar studies in Iran [50][51][52][53], the prevalence of PPD was estimated 15-41%. In the present study, Examining the homogeneity of the distribution of quantitative and qualitative variables in high PPD symptoms vs. low PPD symptoms groups showed that only the energy intake variable was different in the two groups, so that energy intake was significantly higher in low PPD symptoms women.…”
Section: Discussionmentioning
confidence: 95%